The Relationship of Anxiety and Stress With Working Memory Performance in a Large Non-depressed Sample - Lukasik, Karolina M.; Waris, Otto; Soveri, Anna; Lehtonen, Minna; Laine, Matti (Frontiers in Psychology, 2019)
Clinical anxiety and depression as well as acute stress caused by major life events have well-documented detrimental effects on cognitive processes, such as working memory (WM). However, less is known about the relationships of state anxiety, depressive symptoms or everyday stress with WM performance in non-clinical populations. We investigated the associations between these three factors and three WM composites (verbal WM, visuospatial WM, and n-back updating performance) in a large online sample of non-depressed U.S. American adults. WM performance was negatively associated with anxiety and less so with stress, but not with subclinical depressive symptoms. The implications of WM sensitivity to stress and anxiety are discussed.